Analysis of the Determinants of Capital Adequacy Ratio: The Case of Full-Fledged Islamic Banks in the Gulf Cooperation Council (GCC) - Ali, Abdilatif Mao (European Journal of Islamic Finance, 2019)
This study empirically analyzes bank-level and macroeconomic factors that have impact on the capital adequacy ratio (CAR) of the full-fledged Islamic banks in the Gulf Cooperation Council (GCC) and how they influence the banks’ capitalization decisions. This study covers a six years period ranging from 2013 to 2018. CAR ratio is a key stability indicator that measures the capability of banks to absorb unforeseen losses. To conduct the analysis, secondary data gathered from the annual financial reports of the banks as well from international economic database are used. Using multiple linear regression model, the effect of return on assets (ROA), return on equity (ROE), financing to deposit ratio (FDR), operating expense to operating income (OEOI), bank size (SIZE), non-performing financing (NPF) as bank-specific explanatory variables and economic growth (GDP) and inflation (INF) as a proxy for macroeconomic explanatory variables on the CAR of the banks are studied. Due to multicollinearity issues, ROA is dropped. As a result of the regression analysis, OEO and FDR are observed to positively and strongly impact CAR of the examined banks while SIZE is found to have negative and significant effect. ROE, NPF, GDP and INF demonstrated insignificant influences on the banks’ CAR. This study reveals varying and significant under and over regulatory capitalization decisions across the banks. Additionally, extreme expenditures and financial losses suffered by some banks are also discovered.